2013
DOI: 10.1093/brain/awt171
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting phenotypic traits linked to human resilience to Alzheimer’s pathology

Abstract: Clinico-pathological correlation studies and positron emission tomography amyloid imaging studies have shown that some individuals can tolerate substantial amounts of Alzheimer's pathology in their brains without experiencing dementia. Few details are known about the neuropathological phenotype of these unique cases that might prove relevant to understanding human resilience to Alzheimer's pathology. We conducted detailed quantitative histopathological and biochemical assessments on brains from non-demented in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
321
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 326 publications
(341 citation statements)
references
References 61 publications
18
321
1
1
Order By: Relevance
“…74,75 One of these studies included a discovery microarray approach that identified a number of proteins that are differentially expressed in such subjects, including APP binding protein and regulators of apoptosis, trafficking, cytoskeletal structure, and cell-cycle proteins. 74 Work by Perez-Nievas et al 75 showed more fibrillar and oligomer-positive Ab plaques, increased p-tau oligomers, and glial activation in demented compared with nondemented subjects with underlying AD pathology. In another study, low molecular weight SDSstable Ab oligomers were associated with the postsynaptic density in patients with Alzheimer dementia but not in nondemented HPCs.…”
Section: Discussionmentioning
confidence: 99%
“…74,75 One of these studies included a discovery microarray approach that identified a number of proteins that are differentially expressed in such subjects, including APP binding protein and regulators of apoptosis, trafficking, cytoskeletal structure, and cell-cycle proteins. 74 Work by Perez-Nievas et al 75 showed more fibrillar and oligomer-positive Ab plaques, increased p-tau oligomers, and glial activation in demented compared with nondemented subjects with underlying AD pathology. In another study, low molecular weight SDSstable Ab oligomers were associated with the postsynaptic density in patients with Alzheimer dementia but not in nondemented HPCs.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, this theory fails to explain the discrepancy between amyloid plaque deposition and cogni tive impairment in patients with Alzheimer disease. 5 Clinico pathological correlation studies and positron emission tomography amyloid imaging studies have shown that some individuals can tolerate substantial amounts of Alzheimer disease pathology in their brains without experiencing de mentia. 5 Although the significance of plaque load for Al zheimer disease is still under debate and several groups found the pattern of amyloid plaques to be of limited rele vance for the neuropathological staging of Alzheimer dis ease, results from other laboratories showed a strong correl ation between counts of senile plaques in the hippocampus and cortex and memory function.…”
Section: Discussionmentioning
confidence: 99%
“…5 Clinico pathological correlation studies and positron emission tomography amyloid imaging studies have shown that some individuals can tolerate substantial amounts of Alzheimer disease pathology in their brains without experiencing de mentia. 5 Although the significance of plaque load for Al zheimer disease is still under debate and several groups found the pattern of amyloid plaques to be of limited rele vance for the neuropathological staging of Alzheimer dis ease, results from other laboratories showed a strong correl ation between counts of senile plaques in the hippocampus and cortex and memory function. Glial activation emerged as a likely mediator of neurotoxicity and altered cognition, providing further insight into factors and pathways poten tially involved in human susceptibility or resilience to Al zheimer disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated whether the small repulsive force detected between astrocytes and plaques, strong enough to cause the nearest astrocytes to move a few microns, would disturb g(r) at heavier plaque loads. Whereas in APP/PS1 mice the percentage of brain covered by thioflavin or methoxy-labeled plaques can reach 1%, in humans it ranges between 0.8-6.0%, with an average of around 3% (11,12).…”
Section: Tiered Analysis Of Astrocyte Domain-volume Distribution Aroundmentioning
confidence: 99%